2020
DOI: 10.1186/s12889-020-08899-9
|View full text |Cite
|
Sign up to set email alerts
|

Association between obesity status and successful aging among older people in China: evidence from CHARLS

Abstract: Background: The paper aimed to examine the association between obesity status and successful aging among elderly adults in China and further find gender differences in the effect of components of successful aging on obesity status. Methods: The data came from the follow-up survey(2015) of China Health and Retirement Longitudinal Study (CHARLS) and 4019 dwellers age 60 and over are included. Obesity status were defined by the body mass index (BMI) according to Chinese criteria. Successful aging was defined foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 53 publications
(62 reference statements)
1
20
1
1
Order By: Relevance
“…Furthermore, the relationship between alcohol consumption, successful aging, and depression has been previously deemed important [28], with those not meeting SA criteria turning to alcohol consumption to cope with dissatisfaction and depression. One study linked NSA with low BMI [32], while another showed that older adults who were underweight were more likely to experience depressive symptoms than their normal or overweight counterparts [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the relationship between alcohol consumption, successful aging, and depression has been previously deemed important [28], with those not meeting SA criteria turning to alcohol consumption to cope with dissatisfaction and depression. One study linked NSA with low BMI [32], while another showed that older adults who were underweight were more likely to experience depressive symptoms than their normal or overweight counterparts [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with a BMI >24 were considered as overweight. Patients older than >60 years were considered elderly [ 31 , 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…Aging is related to significant changes in body structure and increased abdominal obesity [96]. Both obesity and aging are marked by low-grade inflammatory state and endocrine changes.…”
Section: Obesity and Response To Anti-pd1 Treatmentmentioning
confidence: 99%